The Approach of English Language Learning: Study Case Grammar - Wardhana, I Gede Neil Prajamukti (Proceedings International Conference on Sustainable Innovation (ICoSI), 2022)
Nowadays, English learning still indicatesto English grammar approach to students and makestudents find their difficult to understand their meaning.The ability of English language as a second language inEnglish learning at the class make the students finddifficult because of their mother language that isIndonesian language. Therefore, it needs to make Englishgrammar approach by study case grammar (Fillmore,1968). This study has been done on the student in DhyanaPura University, English literature program in the 4thsemester in the academic year 2018/2019. There are 13students for the sample of this research by finding theirsentence and based on the case grammar itself. Method ofcollecting data is done by observe the student and givingmaterial of case grammar and give an activity by doingexercise to write case grammar from the students. Thedata is analyzed by checked and made correction of thesentence. This study case grammar, the students gave theexamples of verb words by lecture and the students madesentence and finally, made the correction for students. Inthis study found 9 (nine) of study case grammar, they areagentive, objective, instrumental, dative, locative,benefactive, comitative, factitive and time. In case ofAgentive, example: Fajar prepared the table. Thissentence for Agentive described Fajar (a waiter) as asubject of the sentence